Modelling of the reef benthic habitat distribution within the Cabrera National Park (Western Mediterranean Sea). Issue 3 (3rd July 2021) - Mata, Dulce; Úbeda, Jose; Fernández-Sánchez, Adrián
ABSTRACT: Habitat spatial distribution is essential to know where to focus the protection of the seafloor resources. In this work, the bathymetry and backscatter seabed data show the importance of remote sensing applications and geospatial tools to have detailed information of the areas studied. The highresolution data enable to explore the environmental characteristics of selected Mediterranean habitats. These data were combined with available samples for ground truthing the habitat distribution model in the southeast of Cabrera National Park. The habitat modelling results show the high value of the studied area for ecological research. Unique communities of large filterers, including sponges, ascidians and bryozoans, were detected in this area. This study presents a potential habitat distribution map of the vulnerable reef habitat 1170, protected under the UE-Directive on the conservation of Habitats, Flora and Fauna, on the southeast margin of Cabrera Island.